2022
DOI: 10.1097/cad.0000000000001329
|View full text |Cite
|
Sign up to set email alerts
|

KDM5B regulates the PTEN/PI3K/Akt pathway to increase sorafenib-resistance in hepatocellular carcinoma

Abstract: Lysine-specific demethylase 5B (KDM5B) exerts its tumor-promoting functions in numerous malignancies, although the possible mechanisms by which KDM5B promotes cancer aggressiveness in hepatocellular carcinoma (HCC) have been preliminarily explored, the role of this gene in regulating sorafenib-resistance in HCC has not been studied. Thus, the present study was designed to resolve this problem, and our data suggested that KDM5B was significantly upregulated in the HCC tissues collected from patients with sorafe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Our study showed that KDOAM-25 overcomes the MEK resistance by targeting KDM5B in UM. In a recent study, KDM5B regulates the PTEN/PI3K/Akt pathway to increase sorafenib resistance in hepatocellular carcinoma [ 30 ]. Also, one possible explanation resides in the fact that the small compound KDOAM-25 may eventually be inhibiting the expression of KDM5B, resulting in the upregulation of H3K4me3 and H3K27ac, consequently leading to the sensitivity to the MEK inhibitor in UM.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that KDOAM-25 overcomes the MEK resistance by targeting KDM5B in UM. In a recent study, KDM5B regulates the PTEN/PI3K/Akt pathway to increase sorafenib resistance in hepatocellular carcinoma [ 30 ]. Also, one possible explanation resides in the fact that the small compound KDOAM-25 may eventually be inhibiting the expression of KDM5B, resulting in the upregulation of H3K4me3 and H3K27ac, consequently leading to the sensitivity to the MEK inhibitor in UM.…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinase B (AKT) is a significant downstream effecter of phosphatidylinositol 3‐kinase (PI3K) signaling which directs intracellular signal cascades 171,172 . The PI3K/AKT pathway is a key link that promotes the multidrug resistance of cancers via modulating several pathways, including inhibition of apoptosis, suppression of ferroptosis, and promoting cancer stemness 100,172,173 . It was shown that KDM5B downregulated PTEN, a classic tumor suppressor in many cancers, and activated the PI3K/Akt pathway to promote cancer stemness 100 .…”
Section: The Mechanism Of Lysine‐specific Demethylase Mediated Drug R...mentioning
confidence: 99%
“…171,172 The PI3K/AKT pathway is a key link that promotes the multidrug resistance of cancers via modulating several pathways, including inhibition of apoptosis, suppression of ferroptosis, and promoting cancer stemness. 100,172,173 It was shown that KDM5B downregulated PTEN, a classic tumor suppressor in many cancers, and activated the PI3K/Akt pathway to promote cancer stemness. 100 Chen et al 174 reported that EZH2 suppresses the expression of IGFBP5, which increases radiosensitivity of prostate cancer cells through the PI3K-AKT pathway.…”
Section: Other Mechanisms Of Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Schema 5, Nie and colleagues found that high expression of KDM5B can promote the drug resistance of hepatoma cells to sorafenib; And they found that KDM5B can activate the PI3K/AKT pathway, which can increase the expression level of pro‐stemness biomarkers, including CD133, CD44, and EpCAM, to promote CSC properties. [ 101 ] As is well known, the PI3K/AKT pathway plays an important role in the occurrence and development of various cancers, and CSCs can promote the resistance of various cancer cells to various chemical drugs. This study provides an important theoretical basis for KDM5B in the treatment of chemotherapy resistance.…”
Section: Mechanisms Of Kdm5b‐related Drug Resistance To Cancersmentioning
confidence: 99%